IMPROVING STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXT BY USING JIGSAW TECHNIQUE IN CLASS VII B IN MTsN 2 KUANTAN SINGINGI IN ACADEMIC YEAR 2022 / 2023 - Wati, Elda (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2024)
This research was held in MTsN 2 kuantan Singingi. the reseacher applied the jigsaw as a technique to improve the students’ reading comprehension. Specifically, in understanding descriptive text. The purpose of this research is to what extend is jigsaw technique could influence the students' comprehension in reading descriptive text. The collection data method are observation, test, and interview. The students are given multiple choice. The analyzing data is by using the quantitative method. The data was taken from a written test. The test were given in three cycles. The test was done In the last of every cycle. The research result was taken from the application of the Jigsaw technique. The proof of the test average in cycle one is 58,93, in the second cycle was increased in 77.22 average. While in the third cycle is 83,33. The conclusion of this research is the application jigsaw technique can improve the students' reading comprehension of descriptive text in class VII B IN ACADEMIC YEAR 2022/2023. Penelitian ini dilaksanakan di MTsN 2 kuantan Singingi. Peneliti menerapkan puzzle sebagai teknik untuk meningkatkan pemahaman membaca siswa. Khususnya dalam memahami teks deskriptif. Tujuan dari penelitian ini adalah sejauh mana teknik Jigsaw dapat mempengaruhi pemahaman siswa dalam membaca teks deskriptif. Metode pengumpulan datanya adalah observasi, tes, wawancara. Siswa diberikan pilihan ganda. Penganalisisan data dilakukan dengan menggunakan metode kuantitatif. Data diambil dari tes tertulis. Tes diberikan dalam tiga siklus. Tes dilakukan pada akhir setiap siklus. Hasil penelitian diambil dari penerapan teknik Jigsaw. Terbukti rata-rata tes pada siklus I sebesar 58,93, pada siklus II terjadi peningkatan rata-rata 77,22. Sedangkan pada siklus III sebesar 83,33. Kesimpulan dari penelitian ini adalah penerapan teknik jigsaw dapat meningkatkan pemahaman membaca teks deskriptif siswa di kelas VII B TAHUN PELAJARAN 2022/2023